Hippo Signaling-Mediated Mechanotransduction in Cell Movement and Cancer Metastasis - Chang, Yu-Chiuan; Wu, Jhen-Wei; Wang, Chueh-Wen; Jang, Anna C.-C. (Frontiers in Molecular Biosciences, 2020)
The evolutionarily conserved Hippo kinase signaling cascade governs cell proliferation, tissue differentiation and organ size, and can promote tumor growth and cancer metastasis when dysregulated. Unlike conventional signaling pathways driven by ligand-receptor binding to initiate downstream cascades, core Hippo kinases are activated not only by biochemical cues but also by mechanical ones generated from altered cell shape, cell polarity, cell-cell junctions or cell-extracellular matrix adhesion. In this review, we focus on recent advances showing how mechanical force acts through the actin cytoskeleton to regulate the Hippo pathway during cell movement and cancer invasion. We also discuss how this force affects YAP-dependent tissue growth and cell proliferation, and how disruption of that homeostatic relationship contributes to cancer metastasis.